Kinematic calibration and accuracy compensation method for embodied intelligent disinfection robot - CHENG Jun; FAN Weilong; SHAO Jinyan; ZHOU Xuemei (智能科学与技术学报)
Improving the positioning accuracy and real-time performance of disinfection robots are important prerequisites for achieving embodied intelligence, which is crucial to achieve a high sterilization rate of pathogenic microorganism, and can provide a strong guarantee for the health and safety of hospitals, funeral homes and other places. Therefore, a method for kinematics calibration and accuracy compensation of disinfection robot is proposed. First, a modeling method of kinematic model and error model based on screw theory is proposed. Second, the moving region is divided and the feature point data is sampled. Third, an error identification algorithm based on least square method is proposed, and the identification is realized by sampling data. Finally, the positioning error is compensated to the end position of the robot, and the accuracy compensation is realized. The correctness of the proposed method is verified by simulation experiments. The kinematic calibration and accuracy compensation method proposed can greatly improve the positioning accuracy of disinfection robot while ensuring real-time performance, enhance the level of robot's embodied intelligence, and provide a strong guarantee for improving the killing rate of germs and realizing reliable prevention of special places.